Effects of implementing time-variable postgraduate training programmes on the organization of teaching hospital departments. (3rd October 2018) - van Rossum, Tiuri R.; Scheele, Fedde; Sluiter, Henk E.; Paternotte, Emma; Heyligers, Ide C.
Abstract: Introduction: As competency-based education has gained currency in postgraduate medical education, it is acknowledged that trainees, having individual learning curves, acquire the desired competencies at different paces. To accommodate their different learning needs, time-variable curricula have been introduced making training no longer time-bound. This paradigm has many consequences and will, predictably, impact the organization of teaching hospitals. The purpose of this study was to determine the effects of time-variable postgraduate education on the organization of teaching hospital departments. Methods: We undertook exploratory case studies into the effects of time-variable training on teaching departments' organization. We held semi-structured interviews with clinical teachers and managers from various hospital departments. Results: The analysis yielded six effects: (1) time-variable training requires flexible and individual planning, (2) learners must be active and engaged, (3) accelerated learning sometimes comes at the expense of clinical expertise, (4) fast-track training for gifted learners jeopardizes the continuity of care, (5) time-variable training demands more of supervisors, and hence, they need protected time for supervision, and (6) hospital boards should support time-variable training. Conclusions: Implementing time-variable education affects various levels within healthcare organizations, including stakeholders not directly involved in medical education. These effects must be considered when implementing time-variable curricula.